Dynamics of Caligus rogercresseyi (Boxshall & Bravo, 2000) in farmed Atlantic salmon (Salmo salar) in southern Chile: Are we controlling sea lice?. Issue 3 (15th January 2019) - Mancilla‐Schulz, Jorge; Marín, Sandra L.; Molinet, Carlos
Abstract: Caligus rogercresseyi generates the greatest losses in the salmon industry in Chile. The relationship between salmon farming and sea lice is made up of various components: the parasite, host, environment and farming practices, which make it difficult to identify patterns in parasite population dynamics to define prevention and control strategies. The objectives of this study were to analyse and compare the effect of farming, sanitary practices and environmental variables on the abundance of gravid females (GF) and juveniles (JUV) of C. rogercresseyi on Salmo salar in three Salmon Neighborhood Areas (SNAs) in Region 10, south of Chile. Linear mixed‐effects models of the negative binomial distribution were used to evaluate the effect of the different explanatory variables on GF and JUV. Productive variables were the key drivers explaining the abundance of GF and JUV. Results suggest that C. rogercresseyi is not controlled and JUV are persistent in the three SNAs, and sanitary practices do not control the dissemination of the parasite among sites. Environmental variables had a low impact on sea lice abundance. There is a need to perform analysis for modelling of parasite population dynamics to improve Integrated Pest Management, including changes in the governance to achieve an effective prevention and control.